Acetazolamide in prevention of altitude disease - Paweł Choroszewicz; Anna Maria Dobosiewicz; Nataliia Badiuk (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
Mountain climbing is associated with many risky, life-threatening situations. One of the most common attacking diseases at altitudes above 2500 m is altitude disease (HAI). This disease consists of: acute alpine disease, cerebral oedema and pulmonary oedema at altitude. The best way to prevent altitude diseases is by means of alcomatisation and slow increase in altitude. Climbers should follow the principle "climb high, sleep low". Sometimes, however, time or inability to descend do not allow for acclimatization. In such conditions, it is necessary to use pharmaceuticals that prevent the occurrence of an illness of altitude. The following article discusses research on the most commonly used drug in the prevention of acute mountain disease - acetazolamide. This drug was first used in the 60s of the XX century, demonstrating its effectiveness in the prevention of mountain disease. Since then, it has been the subject of many studies.